A preliminary evaluation on bivariate allometry in active-feeding Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) larvae - Raja Muhammad Zuha Raja Kamal Bashah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The potential use of larval cephalopharyngeal skeleton as an alternative growth indicator in forensic entomology practice was assessed based on its developmental pattern, growth performance, and allometric relationship with the larval body. Chrysomya megacephala (Fabricius, 1794), was used as an experimental species and larval development was studied at ambient temperatures and relative humidity. Larval body size was measured from the furthest part of the head to the last abdominal segment. The cephalopharyngeal skeleton was extracted from the body and measured from the tip of the dorsal bridge to the left face of the dorsal cornu. Daily progression of larval body length and cephalopharyngeal skeleton length showed the latter significantly had slower growth rates. The allometry of the larval body and cephalopharyngeal skeleton showed they were correlated only because both variables increased across the three larval instars, suggesting a spurious correlation. Separate bivariate correlations between the two variables showed only the first instar larvae had a significant (p<0.01) but weak correlation, r=0.33. However, removing the effect of larval instars still produced a statistically significant correlation (p<0.001) albeit with moderate strength, r=0.57. From this study, there was not enough evidence to support the cephalopharyngeal skeleton as an equal or a better alternative to the larval body as a growth indicator.